RYE BREEDING FOR LOW-PENTOSANS AND POSSIBILITY OF ITS USE IN ANIMAL FEEDING - V. D. Kobyliansky; O. V. Solodukhina; I. V. Lunegova; S. P. Novikova; M. S. Hlopyuk; V. I. Makarov (Труды по прикладной ботанике, генетике и селекции, 2018)
The strategy and technology of rye breeding for low water-soluble arabinoxilans (WS-AX) in grain were proposed. Together with breeders from other institutions we developed the first six low-pentosan varieties of winter rye suitable for grain forage use. Seeds of low-pentosan forage rye do not form viscous mucus in animal stomachs, thus eliminating the problem that exists when feeding classic baking rye. When using them as fodder for laboratory and farming animals, high palatability and nutritional value were observed.